Hodnocení bakteriálni kolonizace spojivkového vaku pacientů lécených intravitreálními injekcemi anibizumabu - Studnicka, J; Beránek, J; Rysková, L; Rencová, E; Hejsek, L; Rozsíval, P (Ceska a slovenska oftalmologie, 2012)
AIM: To establish the conjunctival sac bacterial flora structure in patients with wet form of the age-related macular degeneration (ARMD) indicated for the intravitreal application of Ranibizumab (Lucentis, Novartis Pharma AG). To evaluate the efficacy of combined local preparation with broad-spectrum antibiotic moxifloxacine 0.5% (Vigamox, Alcon) and povidone iodine solution, 5% (Betadine, Egis Pharmaceuticals, LTD.) and to evaluate subjective toleration of moxifloxacin. MATERIALS AND METHODS: In a prospective, non-randomized study were evaluated 20 eyes of 20 patients treated by means of intravitreally-applied ranibizumab. In all patients, the swabs from the conjunctival sac of the treated eye were repeatedly taken in a given time-schedule--before the start of using moxifloxacin, on the day of the intravitreal application of ranibizumab--before the irrigation of the conjunctival sac with povidone iodine solution, 5%, further after the irrigation--immediately before the injection and the control was token three days after the intravitreal injection. At the same time, the moxifloxacine toleration was evaluated by a questionnaire. RESULTS: The samples taken from the conjunctival sac of the treated eye before the application of moxifloxacine had positive bacterial culture in 17 eyes (85%) and negative culture in 3 eyes (15 %). Furthermore, in 2 eyes with positive culture, there was established resistance to moxifloxacine. After 3 days of moxifloxacine application, there was negative culture in 13 eyes (65%), in 7 eyes (35%) was the bacterial cultivation positive. After the irrigation with povidone iodine 5% solution was the cultivation negative in 17 eyes (85%), positive cultivation was in 3 eyes (15%); in all three cases, the cultures were susceptible to moxifloxacine. Three days after the intravitreal injection, the negative cultivation from the conjunctival sac was found in 13 eyes (65%), and in 7 eyes was the cultivation positive; the cultivated bacteria were moxifloxacine susceptible. Subjective symptoms after moxifloxacine application were reported by 10 patients altogether; 5 patients were without symptoms and 5 patients did not return the questionnaire. On average, the symptoms started the second day of moxifloxacine treatment and the average grade of symptoms was 1.6 on the scale from 0 to 5. CONCLUSION: In our group we found a broad spectrum of microorganisms colonizing the conjunctival sac of patients indicated to the ARMD intravitreal treatment. After the prophylaxis with moxifloxacine, the incidence of positive bacterial cultivation decreased and the povidone iodine 5% solution irrigation this effect increased. The most common pathogen species was Staphylococcus coagulasis negative. Although the resistance to moxifloxacine in two different bacteria in two eyes in the beginning of observation was established, after moxifloxacine treatment, the cultivation of these bacteria in both eyes was negative, and in all other cases the cultivated bacteria were susceptible to moxifloxacine.
Keywords: senioři; Quinolines; injekce intravitreální; bakteriální léková rezistence; Anti-Bacterial Agents; Povidone-Iodine; Drug Resistance, Bacterial; Bacteria; Intravitreal Injections; Wet Macular Degeneration; mužské pohlaví; Ranibizumab; Drug Combinations; Moxifloxacin; fixní kombinace léků; aza sloučeniny; ženské pohlaví; fluorochinolony; Humans; konjunktiva; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; Fluoroquinolones; Aza Compounds; antibakteriální látky; moxifloxacin; ranibizumab; vlhká makulární degenerace; jodovaný povidon; Female; Aged; Conjunctiva; chinoliny; lidé; Male